The community structure of Echinodermata (Echinoidea and Holothuroidea) on seagrass ecosystem in Gunungkidul, Yogyakarta, Indonesia - Nurcahyo, Furqon Darma; Zen, Hafizh Muhamad; Nur ‘Azizah, Husna’ Putri; Nugroho, Gilang Dwi; Ramdhun, Devesee; Yap, Chee Kong; Indrawan, Muhammad; Setyawan, Ahmad Dwi (Society for Indonesian Biodiversity, 2024)
Nurcahyo FD, Zen HM, ‘Azizah HPN, Nugroho GD, Ramdhun D, Yap CK, Indrawan M, Setyawan AD. 2024. The community structure of Echinodermata (Echinoidea and Holothuroidea) on seagrass ecosystem in Gunungkidul, Yogyakarta, Indonesia. Biodiversitas 25: 4561-4571. Echinoderms, which encompass various classes such as sea urchins and sea cucumbers, play a crucial role in marine ecosystems and contribute significantly to maintaining ecological balance. Therefore, this study was conducted to understand the composition structure of echinoderms (Echinoidea and Holothuroidea) in several beaches of Gunungkidul, Yogyakarta, Indonesia. The survey was conducted on March 2024 at Pringjono Beach, Dadap Ayam Beach, Ngrenehan Beach, Torohudan Beach, and Ngrawah Beach. Data analyzed included species diversity, density and ecological indices of echinoderms (Echinoidea and Holothuroidea) at each beach location. The research findings revealed that across the five beaches of Gunungkidul, Yogyakarta, Indonesia, there were two classes of echinoderms, namely Echinoidea (sea urchins) and Holothuroidea (sea cucumbers), with a total of 7 identified species, namely Echinometra mathaei, Echinometra oblonga, Heterocentrotus trigonarius, Tripneustes gratilla, Colobocentrotus atratus, Stomopneustes variolaris, and Holothuria leucospilota. Only one beach recorded the presence of sea cucumbers, while the number of sea urchin species varied at each beach. Dadap Ayam Beach recorded the highest number of sea urchin species, followed by Ngrenehan Beach. Additionally, Dadap Ayam Beach exhibited higher values of species diversity and richness compared to other beaches. A total of seven echinoderm species were identified, with a total abundance of 367 individuals/1000 m2. The beaches in this study showed variations in the diversity and distribution of echinoderms, particularly Echinoidea and Holothuroidea. However, overall species diversity and richness values were generally low, indicating the potential vulnerability of these ecosystems.